The Relationship Of Self-Esteem With Diabetes Distress In Type 2 Diabetes Mellitus Patients - Kurniyawan, Enggal Hadi; Ahmad, Intan Faradela; Widayati, Nur; Wuryaningsih, Emi Wuri; Dewi, Erti Ikhtiarini (Al-Hijrah Indonesia, 2023)
Living with diabetes can lead to various psychosocial problems that affect health and the ability to manage diabetes. Diabetes is a disease that must be managed every day by patients, causing increased stress. This study aimed to analyze the relationship between self-esteem and diabetes distress in patients with type 2 diabetes mellitus. This study used an analytical observational design with a cross-sectional method. The sample in this study was 84 type 2 DM patients. Sampling was carried out in this study using a non-probability sampling technique using consecutive sampling. Self-esteem is measured using the Rosenberg Self-Esteem Scale (RSES), while diabetes distress is measured using the Diabetes Distress Scale (DDS). Data analysis in this study used the Spearman rank (rs) statistical test. Respondents in this study had low self-esteem, as many as 51 people (60.7%). The diabetes distress respondents were in the moderate distress category, as many as 43 people (51%). Based on the results of the study, it was found that there was a significant relationship between self-esteem and diabetes distress in type 2 DM patients with a correlation value of -0.548, which means that the direction of the correlation is negative with moderate strength. This shows that the higher the self-esteem of type 2 DM patients, the lower the diabetes distress experienced. Nurses are expected to think about psychological aspects by providing counseling interventions to patients to increase self-esteem to reduce diabetes distress experienced by patients.